Falls and Physical Activity among Cataract Patients in Vietnam. (2nd January 2022) - To, Quyen; Huynh, Van-Anh; Do, Dung; Do, Vu; Congdon, Nathan; Meuleners, Lynn; Vandelanotte, Corneel; Hong, Hiep; Nguyen, Ho; To, Kien
ABSTRACT: Purpose: To investigate the relationship between falls, physical activity, and other socio-demographic and visual factors among cataract patients in Ho Chi Minh City, Vietnam. Methods: A cross-sectional study was conducted between April and November 2018. Patients presenting to two hospitals with age-related unilateral or bilateral cataract, aged ≥50 years, literate, and scheduled for a first-eye cataract surgery were recruited. The International Physical Activity Questionnaires short form was used to measure physical activity. Visual disability score was self-reported using the Catquest-9SF. The number of falls in the last 12 months prior to data collection were self-reported. Visual acuity and contrast sensitivity were measured using standard protocols. Results: A total of 340 patients had complete data, the majority of whom were women (62.4%), living with a spouse (66.5%), had an education level of Grade 5 or below (68.2%), and a monthly income from medium to high (58.5%). Average age was 65.7 years. A total of 135 falls were reported in the last 12 months with 27.6% reporting ≥1 fall and 7.1% ≥2 falls. Persons with high (adjusted Prevalence Ratio (aPR) = 2.4, 95%CI = 1.2, 4.7) and low (aPR = 2.4, 95%CI = 1.2, 4.6) physical activity levels had more falls compared to those with moderate levels. Women (aPR = 1.7, 95%CI = 1.04, 2.7) and those with medium income (aPR = 2.9, 95%CI = 1.2, 6.9) were more likely to fall. Poor binocular logMAR visual acuity with habitual correction (aPR = 2.3, 95%CI = 1.1, 4.6) and poor visual disability scores (aPR = 1.4, 95%CI = 1.02, 2.0) were associated with falling. Conclusion: Patients with a moderate level of physical activity were less likely to fall compared to those with low or high levels although this U-shape relationship needs to be further investigated in prospective interventional trials. Men and those with high monthly income, better visual acuity and visual disability score were also less likely to fall. Cataract patients might be advised to maintain a moderate level of physical activity while waiting for surgery. Strategies to prevent falls may also prioritise cataract surgery for women and those with lower income.